MOTIVATION, STYLES AND STRATEGIES - Perez-Barriga, Marla (European Scientific Journal, ESJ, 2013)
Throughout the history of foreign languages teaching has been observed using different methods and approaches, role of teachers and students, researches and results in acquiring a second language. Those factors have contributed to improve student’s learning process. Nowadays adopting or opt more for a communicative approach which develops the use of language through meaningful and relevant tasks for the student. It is also important to take into account or consider other critical factors such as knowledge or to know that students have their own type of motivation, style and learning strategies. According to Tobias (1994): ‘ Each of us perceives the world differently, in a unique way, consistent with our own style shaped by multiple factors, and that leads us to have our own preferences and skills, as well as our own weaknesses and deficiencies ’.